Implementasi Fuzzy Logic pada Sistem Sortir Otomatis Alat Penghitung Jumlah Buah Apel - Rana Angely Syawalia; Sabilal Rasyad; Destra Andika Pratama (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Indonesia is an agrarian country that has abundant natural resources, especially in agriculture. One of the is the local apple which comes from Kota Batu. Apples from Kota Batu are recognized as having delicious and fresh flavors. The Land itself has the area of 2,993.88 Ha, which means that Indonesia should have been able to export apples from Kota Batu. the production process that still using human power (conventional) in the sorting process is one of the problem for Indonesia to be able to export local apple products. To increase the economic value of local apple, especially in global market is sorting. Based on these problems, an automatic sorting system that can separate the types of apples based on weight and color was created. This system uses fuzzy logic method for sorting process, where the tool will sort automatically based on the decision rules that have been given using the If-Then algorithm. The data processing controller is Arduino Mega 2560. The main input data is from load cell sensor and color sensor TCS3200. While the sorting executor is in the form of two servo motor MG996.